2008
DOI: 10.1021/om800114a
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Selectivity-Determining Factors in the Phosphine-Free Heck Arylation of Allyl Ethers

Abstract: The Heck reaction of aryl iodides and bromides with allyl ethers has been investigated. Using phosphine-free Pd(OAc)2 in DMF at 90 °C in the presence of Bu4NOAc, the reaction gave cinnamyl derivatives, usually in good to high yields, with a wide range of aryl halides. The reaction tolerates a variety of functional groups, including ether, amide, alcohol, aldehyde, ketone, ester, cyano, carboxylic acid, and nitro groups. Ortho-substituted arylating agents afforded moderate yields in some cases, though good to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…The wider applicability of aryl bromides is undisputed in cross‐coupling reactions, whereas few results have been described for the MH reaction of aryl bromides with allyl ethers 9c,e. We were pleased to note that under our optimized reaction conditions aryl bromides also reacted with phenols and allyl chloride albeit with increasing catalyst loading and reaction temperature to provide the desired products in moderate yields (Scheme ).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…The wider applicability of aryl bromides is undisputed in cross‐coupling reactions, whereas few results have been described for the MH reaction of aryl bromides with allyl ethers 9c,e. We were pleased to note that under our optimized reaction conditions aryl bromides also reacted with phenols and allyl chloride albeit with increasing catalyst loading and reaction temperature to provide the desired products in moderate yields (Scheme ).…”
Section: Methodsmentioning
confidence: 94%
“…To avoid using the corresponding cinnamyl derivatives as substrates, the Mizoroki–Heck‐type reaction of allyl ethers with aryl halides is extensively applied to synthesize cinnamyl ethers 9. Norrby et al 9c. reported that cinnamyl alcohol derivatives could be obtained in high yields by the palladium‐catalyzed Mizoroki–Heck (MH) reaction of aryl iodides or bromides with 2‐(allyloxy)tetrahydropyran.…”
Section: Methodsmentioning
confidence: 99%
“…Because the chloride is site labile, [10] the chloride in 1 a is expected to easily switch position and to be in rapid equilibrium with the slightly more stable 1 c in which the empty coordination site is trans to the very strongly trans-influencing [11] hydride. This complex is in itself not a catalyst because the bulky phosphine ligand in the cis position to the vacant site on palladium renders coordination of the alkyne impossible, and because the alkyne and the hydrogen must be positioned cis to each other for hydropalladation to occur.…”
Section: Resultsmentioning
confidence: 99%
“…Norrby and co-workers have demonstrated, by deuterium labelling, that the carbinol hydrogen can undergo elimination. 24 The reaction conditions were modified in an attempt to obtain the thermodynamically favoured a,b-unsaturated carbonyl compounds. Thus, the reaction of aryl bromide 2 and allylic alcohol 3 was performed in the presence of oxygen with the goal of promoting a second insertion of palladi- a Reaction conditions: aryl bromide (1 mmol), allylic alcohol (1.1 mmol), NaOAc (1.2 mmol), catalyst 1 (1 mol%), DMF, 90°C, 6 h. b Yield of isolated product after chromatographic purification.…”
Section: Scheme 1 Phosphinito Complex Of Palladium(ii)mentioning
confidence: 99%
“…7,161.9,151.7,123.6,109.0,39.2,35.7,22.2,7.5. MS (EI): m/z (%) = 180 14, 123 (100), 109 (30), 57 (23), 28 (24).…”
Section: -[(E)mentioning
confidence: 99%